Domestication of Arabo-Islamic Words in the Ilọrin Dialect of Yorùbá - Abdulrazaq Mohammed Katibi (Yoruba Studies Review)
Language is a dynamic phenomenon which develops-among other things with the introduction of new concept. Yoruba language-like many other living languages- has developed for its ability to accommodate new concepts into its vocabulary. With the introduction of Islam to many parts of the world, Arabic becomes the instrument to convey its concepts. Some of these concepts are either adopted as a loan word or being literally translated. However, Yoruba dialect spoken in Ilorin adopts a strategy of domesticating some of the Arab-Islamic words despite the fact that some of these concepts do not exist in Yoruba Language. This work therefore aims at identifying and trace the origin of the domesticated Arabic of Islamic concept popularly used in the dialect of Ilorin people. Forty (40) of such words are selected in the areas of Islamic doctrine, civilization and materials. Meanwhile simple percentage is used to analyze some variables in the work. After the study it is discovered that the heterogenic composition of Ilorin assisted in the domestication of Islamic concept from Arabic. A sizeable of them are from Yoruba origin coined and adopted from Yoruba while some of these words are from other Languages. Interestingly these words only do not find their ways in Yoruba dictionary but are also regularly used among Yoruba people in Nigeria. It is recommended that further studies should be conducted in this area for the purpose of enriching relationship between Arabic and Yoruba Languages.